2009
DOI: 10.1063/1.3077163
|View full text |Cite
|
Sign up to set email alerts
|

The photophysics of singlet, triplet, and degradation trap states in 4,4-N,N′-dicarbazolyl-1,1′-biphenyl

Abstract: In this paper we report the results of optical characterization of 4,4-N,N′-dicarbazolyl-1,1′-biphenyl (CBP), known as a host material for phosphorescent light emitting devices. Using absorption, steady state, and time-resolved spectroscopy, we explore the singlet and triplet states in solid and solution samples of CBP. In solutions we observe two distinct short-lived states with well-resolved emission originating from individual molecule singlet states (at 365 and 380 nm) and “quenching” low energy (LE) state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
2
27
0
1
Order By: Relevance
“…When we record the emission spectrum of spincoated film of P2VK, we observed emission only at 525 nm, irrespective of which wavelength we excited, indicating increased energy transfer via migration. This is very similar to previously observed behaviour of polyfluorene40 or 4,4'‐ N , N ′‐dicarbazolyl‐1,1′‐biphenyl38 containing low energy trap states.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…When we record the emission spectrum of spincoated film of P2VK, we observed emission only at 525 nm, irrespective of which wavelength we excited, indicating increased energy transfer via migration. This is very similar to previously observed behaviour of polyfluorene40 or 4,4'‐ N , N ′‐dicarbazolyl‐1,1′‐biphenyl38 containing low energy trap states.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, by using sensitized phosphorescence quenching Klopffer et al22 have shown that these traps are populated via the triplet channel, probably by Dexter transfer, which is very reasonable in films where emissive sites can be within angstroms of each other, thus making this transfer much more efficient than in solutions, even if highly concentrated. The concentration of trap species might be extremely low, in the range of 5 × 10 −3 % as conjectured by Klopffer et al22 Hopping is very efficient in these types of films and triplets have long lifetimes to enable them to find a trap easily 36–38. However Chakrabarty et al23 estimate that nearly all carbazoles are paired at 10 K. Benten et al39 have performed calculation on bridged carbazole pairs, pointing out that the large red shift of the monomer to dimer phosphorescent cannot be simply attributed to excitonic delocalisation; substantial charge resonance effects must contribute, with large orbital overlap between the pairs.…”
Section: Resultsmentioning
confidence: 97%
“…But, because the conduction band minimum and the valence band maximum of InP QDs are higher than those of CdSe QDs, there are large hole injection barrier and small electron blocking barrier between InP QDs and CBP layers ( Figure a) . In Figure a, there is an additional emission peak at about 400 nm for the device with CBP HTL due to the electron–hole recombination in CBP layer caused by the unbalance of charge injection . To eliminate this additional emission peak, we used another HTL material, TAPC, which shows small hole injection barrier between TAPC and MoO 3 and large electron blocking barrier between TAPC and InP QDs (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The PH spectra identified at long TD is clearly the PH of the host, CBP, having three well defined peaks (at 491 nm, 518 nm and 557 nm) with increasing emission intensity on cooling down the system. 27,28 In this thin film, the excited states were not confined on the DPO-TXO2 molecules, and a quenching of fluorescence was observed by the host. Therefore, the 1 CT was identified to be at 2.82 eV and the 1 LED level was not identified.…”
Section: Solid State Propertiesmentioning
confidence: 94%